The roles of veterinary, medical and environmental professionals to achieve ONE HEALTH - Pal, Mahendra; Gebrezabiher, Weldegebrial; Rahman, Md. Tanvir (Journal of Advanced Veterinary and Animal Research, 2014)
According to the WHO- Health is a state of complete physical, mental and social well-being and not merely an absence of disease or infirmity. The good health is the fundamental right of all the people on earth. The concept of One Medicine coined by Calvin W. Schwabe evolves towards One Health which comprises collaborative efforts of multiple disciplines to achieve perfect health of people, animals, and our environment. One Health deals with the challenges at the intersection of animal, human and environment health including the infectious diseases, the global food crises, and climate change due to global warming. The cordial and active association of various disciplines such as medicine, veterinary, public health, environment, wildlife, ecology, and food hygiene is highly emphasized in order to achieve the goal of One Health. This mini-review describes brief history of one health, the roles of veterinary, medical and environmental professionals, and developing collaboration with various concern professionals to achieve one health. In addition, the selected achievements of one health in the past 10 years have been described along with the challenges ahead for the successful implementation of such concept. http://dx.doi.org/10.5455/javar.2014.a27